ARTISTIC ORIGINALITY OF D. RUBINA'S STORY THE DOG (Spectrum Journal of Innovation, Reforms and Development, 2025)
The article analyzes the artistic world in the story "The Dog" by D. Rubina. The author's attention is focused on sensory poetics, the specifics of extra-plot elements, symbolism, coloristics and landscape, onomastics.